A Comparative Study of the Concept of the Pen in the Views of Zaydari Nasawi, Najm-e-Razi and Nasir Khosraw-e-Balkhi - Shafaq, Mohammad Musa; Ebtihaj Hojjati, Mohammad Amin (Journal of Social Sciences - Kabul University, 2025)
In the realm of Persian Dari prose literature, the book Nafthat al-Masdur stands out as one of the most stylistically crafted works. Among mystical prose texts, Mirsad al-‘Ibad closely approaches literary technicality in its form. The book Zad al-Musafirin by Nasir Khusraw is characterized by its theological and philosophical content. In all three works, the concept of the pen holds a significant and elevated position. In Nafthat al-Masdur, the pen is emphasized at the opening of the text; in Mirsad al-‘Ibad, at the beginning of creation; and in Zad al-Musafirin, the pen is referred to metaphorically through the act of writing. Writing in this latter work is portrayed as a symbol of civilization, regarded as more important than spoken language. The present article explores various dimensions of the pen across these three texts. It begins by examining the importance of comparative studies in literary research, then addresses the role of the pen in each individual work, followed by an analysis of the similarities and differences in their perspectives. The research method employed is library-based and analytical-descriptive.